Mobile public warning in Japan and the United States: a sister cities collaboration - Bean, Hamilton; Takenouchi, Kensuke; Cruz, Ana Maria (Frontiers in Communication, 2025)
Over the last decade, countries have adopted or expanded the use of cell broadcast systems to support mobile public warning for natural and human-caused hazards and disasters. Cell broadcast entails sending short messages simultaneously to multiple mobile devices in a defined geographic area. Japan and the United States have pioneered the development of mobile public warning technology, yet both countries continue to experience problems with the nonuse, misuse, or misunderstanding of these systems. To explore prospects for improving this situation, this study presents thematic analyses of official documents and transcripts from four Japan-U.S. meetings and workshops with researchers, officials, and residents in the “sister cities” of Yamagata, Yamagata Prefecture, Japan, and Boulder, Colorado, USA. The study’s boundary spanning, cross-national findings contribute new insights regarding the appropriate level of local adaptation versus global standardization of mobile public warning theory, policy, and practice. These findings can aid officials who are increasingly relying on mobile public warning systems to help keep communities safe amid the intensifying impacts of climate change.